Clinical Screening of Congenital Heart Disease in Neonates: a Literature Review on Five Studies - Bentito Zulyan Pamungkas; Phaleno Pramasditomo Widaryo (The Avicenna Medical Journal, 2022)
Background: Diagnosing Congenital Heart Disease (CHD), particularly critical CHD in newborns, could be difficult but crucial, since the field of congenital heart surgery has shifted from initial palliation followed by final correction at a later age to stressing early repair even in the youngest individuals. Although echocardiography remains the gold standard for diagnosing CHD, simple clinical examination may be helpful in screening neonates who require further investigation and treatment. In this study, we searched and reviewed the literature on clinical screening for CHD using a simple, affordable tool that is readily available in primary health care facilities, to prove that early simple clinical examination would help physician to screen for asymptomatic CHD.Methods: We searched articles on google scholars that discuss clinical screening of CHD in neonates. Inclusion criteria is articles published within five years and exclusion criteria is articles published older than five years.Results: We found five articles eligible and pick consecutively. We found that pulse oximetry sensitivity and specificity ranged from 21.54%-77.3% and 82.65%-99.9%, respectively. Cardiac auscultation with murmur of grade ≥2 as count as positive, having high range of sensitivity and specificity, with sensitivity ranged from 17.3%-89.58% and specificity ranged from 47.36%-99.69%. When pulse oximetry and cardiac auscultation combined, three studies found that the sensitivity and specificity increased dramatically, 89.9%-95.5%, 94.7%-99.37%, respectively. Conclusion: Both cardiac auscultation and pulse oximetry was an easy, feasible method with readily available basic tools at all hospital with acceptable sensitivity and specificity to screening CHD before suspected neonates undergo echocardiography, therefore making CHD diagnosed more effective and efficient.